Antibacterial Activity of Jambi Forest Honey on Cariogenic Bacteria Lactobacillus acidophilus (Nusantara Science and Technology Proceedings, 2022)
Caries is a major dental and oral health problem in Indonesia because of their high prevalence. Based on the 2018 Basic Health Research in Indonesia, the prevalence of caries in Indonesia is 88.8%. Dental caries is a local destructive on dental hard tissue caused by the presence of acids produced from bacterial metabolism in dental plaque. The use of mouthwash has an important role in maintaining dental and oral hygiene, especially in reducing bacteria in plaque. A study showed that gargling with honey can reduce plaque scores in the oral cavity. This study aims to determine the antimicrobial effect of Jambi forest honey on cariogenic bacteria. The caries-causing bacteria used in this study was Lactobacillus acidophilus. This research is an in vitro experimental study using the disk diffusion method to obtain the effectivity of Jambi forest honey to inhibit cariogenic bacteria. The inhibition of Jambi forest honey will be compared with antiseptic mouthwash containing 0.2% Chlorhexidine gluconate, antiseptic mouthwash containing 21.6% alcohol, branded honey, and control. In this study, all of the agar media was repeated 6 times in each treatment group. The analysis was carried out using the one-way ANOVA test to see the comparison of inhibition in these five treatment groups. In Lactobacilus acidophilus, Jambi forest honey was effective as an antimicrobial compared to control, branded honey, and mouthwash containing alcohol with p-values respectively 0.002; 0.007, and 0.0003. Based on the results of this study, Jambi forest honey was effective to inhibit the growth of cariogenic bacteria Lactobacilus acidophilus.